2011
DOI: 10.1371/journal.ppat.1002091
|View full text |Cite
|
Sign up to set email alerts
|

13C Metabolic Flux Analysis Identifies an Unusual Route for Pyruvate Dissimilation in Mycobacteria which Requires Isocitrate Lyase and Carbon Dioxide Fixation

Abstract: Mycobacterium tuberculosis requires the enzyme isocitrate lyase (ICL) for growth and virulence in vivo. The demonstration that M. tuberculosis also requires ICL for survival during nutrient starvation and has a role during steady state growth in a glycerol limited chemostat indicates a function for this enzyme which extends beyond fat metabolism. As isocitrate lyase is a potential drug target elucidating the role of this enzyme is of importance; however, the role of isocitrate lyase has never been investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
181
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(197 citation statements)
references
References 45 publications
15
181
0
1
Order By: Relevance
“…1). This pattern was indicative of an activation of M. tuberculosis isocitrate lyases (ICLs), which serve dual roles in the glyoxylate shunt and methylcitrate cycles, and have previously been reported to be up-regulated in M. tuberculosis in response to hypoxia and essential for survival of bacillus Calmette-Guérin at low growth rates (37,38). Accordingly, we observed a hypoxia-induced increase in icl transcript levels even when M. tuberculosis was already metabolizing acetate ( Fig.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…1). This pattern was indicative of an activation of M. tuberculosis isocitrate lyases (ICLs), which serve dual roles in the glyoxylate shunt and methylcitrate cycles, and have previously been reported to be up-regulated in M. tuberculosis in response to hypoxia and essential for survival of bacillus Calmette-Guérin at low growth rates (37,38). Accordingly, we observed a hypoxia-induced increase in icl transcript levels even when M. tuberculosis was already metabolizing acetate ( Fig.…”
Section: Resultsmentioning
confidence: 92%
“…ICLdeficient M. tuberculosis is one of the most severely attenuated mutants tested in a mouse model of TB. Such attenuation may reflect the loss of multiple functions, some of which were revealed by metabolomic studies and could not be foreseen by genetic or bioinformatic approaches (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…The glyoxylate shunt enzymes isocitrate lyase (20,21) and malate synthase (22) are good examples and are currently being explored as drug targets. Similarly, Beste et al recently showed that anaplerotic reactions are likely to be important during infection (23). This is corroborated by the fact that inhibitors of carbonic anhydrase were shown to have an antibiotic effect on M. tuberculosis (24).…”
Section: Current Target-based Drug Discovery In Mycobacterium Tubercumentioning
confidence: 82%
“…This suggests that Pck might contribute to regulation of metabolic adaptations of MTb central metabolism in response to changing environments (9,12,14). In this study, we set out to systematically investigate in vitro reaction conditions that influence the activity of the Pck anaplerotic and gluconeogenic reactions and could thus regulate the PEP-OAA node in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, infection of primary macrophages and mice with a Pck knock-out MTb strain were impaired, demonstrating the gene's pivotal role for MTb infection and for persistence of MTb in mice (12,13). Although the requirement for Pck was linked to the enzyme's gluconeogenic (anabolic) function, in vitro studies under hypoxic and growth-limiting conditions demonstrated its anaplerotic function in MTb (9,14). Additionally, a recent study applying 13 C labeling during THP1 cell infection with a Pck knock-out strain demonstrated that Pck contributes to carbon fixation in MTb (15).…”
Section: Mycobacterium Tuberculosis (Mtb)mentioning
confidence: 99%